ALK-R3HDM1 and EML4-ALK fusion as a mechanism of acquired resistance to gefitinib: A case report and literature review - Zeng, Zhu; Wang, Tao; He, Junjun; Wang, Yuehong (Frontiers in Oncology, 2022)
We report a case with a novel ALK-R3HDM1 and EML4-ALK dual fusion that might be a delicate mechanism for acquired resistance of EGFR-TKI. A patient with EGFR L858R lung adenocarcinoma developed diseases progression after 72.7 months of gefitinib therapy, re-biopsy was done and the next-generation sequencing (NGS) showed the disappearance of the previous EGFR mutations, and two new ALK fusions emerged, indicating that the emergence of dual ALK rearrangement may be the underlying mechanism of gefitinib resistance. The patient exhibits an excellent response to second-line alectinib treatment with a significant clinical benefit and a high quality of life. Finally, we summarized previous studies in which ALK fusion is a required resistance mechanism to EGFR-TKI.